2021
DOI: 10.1596/1813-9450-9659
|View full text |Cite
|
Sign up to set email alerts
|

Trade Impacts of Intellectual-Property-Related Ptas: Evidence from using the World Bank Deep Trade Agreements Database

Abstract: The Policy Research Working Paper Series disseminates the findings of work in progress to encourage the exchange of ideas about development issues. An objective of the series is to get the findings out quickly, even if the presentations are less than fully polished. The papers carry the names of the authors and should be cited accordingly. The findings, interpretations, and conclusions expressed in this paper are entirely those of the authors. They do not necessarily represent the views of the International Ba… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

4
16
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(20 citation statements)
references
References 16 publications
4
16
0
Order By: Relevance
“…Our focus on non-OECD reforming countries reflects the clear distinction between countries within and outside of the OECD in the context of IPRs institutions. In general, non-OECD countries have strongly opposed TRIPS-plus standards and have agreed to implement them only as a concession when negotiating PTAs (Greppi & Naghavi, 2022;Maskus & Ridley, 2021;Sell, 2010). In contrast, the US, EU, and EFTA have systematically required core aspects of TRIPS-plus standards to be included in their agreements (Maskus & Ridley, 2020, 2021.…”
Section: Ptas and Iprs Reformmentioning
confidence: 99%
See 3 more Smart Citations
“…Our focus on non-OECD reforming countries reflects the clear distinction between countries within and outside of the OECD in the context of IPRs institutions. In general, non-OECD countries have strongly opposed TRIPS-plus standards and have agreed to implement them only as a concession when negotiating PTAs (Greppi & Naghavi, 2022;Maskus & Ridley, 2021;Sell, 2010). In contrast, the US, EU, and EFTA have systematically required core aspects of TRIPS-plus standards to be included in their agreements (Maskus & Ridley, 2020, 2021.…”
Section: Ptas and Iprs Reformmentioning
confidence: 99%
“…Throughout the early 21st century, the US, EU, and European Free Trade Association (EFTA) each signed several PTAs with developing countries that mandated so‐called TRIPS‐plus standards. These routinely require strengthened patent protection, more comprehensive copyright protection for digital goods and enhanced infringement penalties (Maskus & Ridley, 2020, 2021). Moreover, these agreements remove much of the legal flexibility afforded to developing countries under TRIPS (Sell, 2010).…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…Some scholars have studied the trade effects of the overall depth of RTAs and demonstrated that an increase in the depth of RTAs has a positive impact on traditional trade [ 2 , 3 ], value chain trade [ 4 , 5 , 6 , 7 ], and the value chain division of labor [ 8 , 9 ]. Meanwhile, some scholars have researched the trade effects of the depth of the terms in RTAs and examined the heterogeneous impacts of the depth of environmental terms [ 10 , 11 ], the depth of digital trade facilitation terms [ 12 ], the depth of intellectual property terms [ 13 ], and the depth of technical trade measures terms [ 14 ] on a country’s foreign trade. Second, regarding the factors affecting residents’ health, scholars have mainly analyzed the internal and external factors that affect residents’ health.…”
Section: Introductionmentioning
confidence: 99%